Medusa’s Head: Boss Rattlers, Rattlesnake Queens, and Goddamn True Love in Harry Crews’s a Feast of Snakes - Hanssen, Ken R. (Studia Anglica Posnaniensia, 2016)
This sombre ending is perhaps what Todorov would term “the realization of an order always preordained,” but it would be a mistake to dismiss it as merely the inevitable outcome of yet another southern boy’s unarticulated rage against modernity. Struggling endlessly like the pitfighting dogs his daddy breeds, Joe Lon, entangled in the determinants of his existence, comes to give mimetic shape to a contemporary American identity both utterly strange and jarringly familiar.